The affinities of the early cynodont reptile, Nanictosaurus - van Heerden, Jacques; Rubidge, Bruce (Bernard Price Institute for Palaeontological Research, 1990)
This investigation into the anatomy of the four extant specimens of Nanictosaurus has revealed that there is one valid species, viz. N. kitchingi Broom 1936 which has two junior synonyms, viz. N. robustus Broom 1940 and N. rubidgei Broom 1940. The closest known relative of Nanictosaurus is the well-known cynodont Thrinaxodon liorhinus. The differences from Thrinaxodon and other early cynodonts are discussed and illustrated.
Keywords: anatomy; taxonomy; Thrinaxodon